Assesing the Financial Performance: in Perspective Environmental Performance, CSR, GCG, and Leverage - Agda Laily Ahadiya (Institut Teknologi Sepuluh Nopember, 2020)
The company has a goal to generate maximum profit. However, the dry season in 2019 used by them to carried out